Multiple segmental uniparental disomy associated with abnormal DNA methylation of imprinted Loci in silver-russell syndrome. - Dias, R; Bogdarina, I; Cazier, J; Buchanan, C; Donaldson, M; Johnston, L; Hokken-Koelega, A; Clark, A (2012)
BACKGROUND: Silver-Russell syndrome (SRS; online inheritance in man 180860) is a low-birth-weight syndrome characterized by postnatal growth restriction and variable dysmorphic features. Although maternal uniparental disomy (UPD) of chromosome 7 and hypomethylation of H19 have been reported in up to 50% of all cases, no unifying mechanism is apparent. SUBJECTS AND METHODS: Ten patients and their parents were studied using the Illumina GoldenGate methylation array and the Illumina 370K HumHap single-nucleotide polymorphism array to identify aberrations in DNA methylation as well as genomic changes including copy number changes and uniparental disomy events. RESULTS: We found evidence of UPD events outside chromosome 7 in all patients. In up to 30% of patients with SRS, DNA methylation changes occur in imprinted gene loci outside 11p15.5 (PEG3, PLAGL1, and GRB10), not previously consistently linked with SRS. Furthermore, hypermethylation of GRB10 was associated with increased mRNA expression. In addition, 20% of patients appear to have DNA methylation abnormalities within multiple loci. Not all the imprinted loci with methylation defects were affected directly by UPD. CONCLUSIONS: The association of widespread UPD associated with abnormal methylation and mRNA expression in imprinted genes in SRS is consistent with the concept of UPD as an initial genomic abnormality leading to unstable DNA methylation within the regulatory network of imprinted genes. Furthermore, disruption of any one of these genes may contribute to the heterogeneous clinical spectrum of SRS.